Multi-Agent Word Guessing Game - Luis, Gabino; Suárez, David; Mateos, Alfonso J. (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2018)
The task of creating algorithms to solve a problem is surely a hard thing as it can be the fact of evaluating them. A well designed algorithm can be very powerful but, it may lack of efficiency at some aspects. This paper proposes a multi-agent system based game with three types of agents: CBot, ABot and QBot, which stands for Coordinator, Answer and Question. They will play a game based on questions and answers, where each of the QBots uses a different algorithm to guess a word. The CBot has the responsibility of the efficiency measurements, receiving and manipulating the ABot reports. The game will finish once all QBots give the correct answer and after that, the efficiency of the algorithms thanks to the CBot. Using this method, it is easier to determine which algorithm is the best with a given performance measurement.